Molecular detection of major coagulase positive Staphylococcus isolates from the canine pyoderma cases - SHOBHA, KHAMBAM; S N, GHODASARA; D B, BARAD; B B, JAVIA; D T, FEFAR; P J, POSHIYA (The Indian Journal of Animal Sciences, 2024)
Pyoderma is a one of the most common dermatological condition frequently observed in small animal practice. The genus Staphylococcus is responsible for approximately 90% of pyoderma cases in dogs, caused by bacterial infection. The purpose of the present study was to investigate the prevalence of major coagulase positive Staphylococcus bacteria causing different types of canine pyoderma in dog breeds. The samples were collected from the clinical cases of canine pyoderma with varying grade from the different breeds of dogs for the molecular based detection of major coagulase-positive Staphylococcus species. Out of total bacterial isolates, majority of them were molecularly identified as Staphylococcus spp. by 16S rRNA gene. Of these Staphylococcus spp., most common isolated organism was S. pseudintermedius (80.82%) followed by S. schleiferi subsp. coagulans (8.22%) and aureus (2.74%), using Pse-nuc, Sch-nuc, and Au-nuc genes, respectively.